Kontribusi Kompensasi Karyawan terhadap Komitmen Karyawan di STIE IBMI Medan - Chon Cho Reynols Manday (Master Manajemen, 2024)
Low compensation given to companies is the cause of low employee commitment to the company. Many organizations are found to consider employees as not their main asset. This is evidenced by the large number of workers complaining about the amount of compensation they receive which is not fair, appropriate and reasonable, so that many employees look for other jobs which they think are more prosperous, ultimately turnover increases, this indicates that company management is unhealthy. The formulation of the problem in this research is How does employee compensation contribute to employee commitment at STIE IBMI Medan. This research aims to find out and analyze how employee compensation contributes to employee commitment at STIE IBMI Medan. Based on observations and interviews, research results show that compensation contributes to employee commitment, meaning that if employee compensation is fair, appropriate and reasonable then employee commitment will increase to the company, so that employees will devote all their energy, thoughts and knowledge to the company to the fullest so that the company can progressing rapidly. The hypothesis in this research is that employee compensation contributes to employee commitment. This research uses a qualitative descriptive method, namely descriptive research that tends to use analysis. Data was obtained by observation and interviews.